Copyright: how to use your photocopier & computer lawfully - Nicholson, Denise Rosemary (South Africa. Department of Sport, Arts & Culture: Librsary and Archive Services Directorate. Free State Provincial Library and Information Service, 2008)
This article gives practical tips when making reproductions for educational purposes.
Keywords: copyright; photocopying;computers